Sentencing Guidelines and Rechterlijk Pardon in Article 54 Paragraph (1) and (2) of the Criminal Code 2023 - Arianda Lastiur Paulina; Eva Achjani Zulfa (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This research examines the regulations and implications of Law No. 1 of 2023 concerning the Criminal Code (KUHP 2023). The study focuses on the application of sentencing guidelines and the authority of judicial pardon, as well as its impact on judges' performance. KUHP 2023, which replaces the Dutch colonial Criminal Code, was created to reflect the dynamic developments in law, society, and technology, as well as the Indonesian legal philosophy based on Pancasila and the 1945 Constitution. The new sentencing guidelines detailed in Article 54, Paragraph (1) of KUHP 2023 are expected to assist judges in considering proportional punishments, while judicial pardon provides flexibility in handling minor cases. This research employs a normative juridical method and secondary data, including legislation, court decisions, and legal literature, to analyze the implementation of sentencing guidelines and judicial pardon, and their implications in Indonesia's criminal procedure law.